Advances by Spanish Operations Management researchers in 2019: the case of ACEDEDOT members - Lidia Sanchez-Ruiz; Elsa Diez-Busto (WPOM : Working Papers on Operations Management, 2020)
Are you a member of an organization that needs to contact a researcher who works on a topic you are interested in? Are you a PhD supervisor trying to identify experts of an specific topic for the Dissertation Committee? Are you thinking about a research / publication project and want to find some new partners to collaborate with? If you answered yes to any of these questions (or similar questions), this work may be of interest to you. The objective of this article is to summarize the research published in 2019 by Spanish researchers in the area of operations management, who are ACEDEDOT members. This will allow us to identify themes that are considered relevant in the context of a country and a specific organizational or social framework. At the same time, it will make it possible to identify groups of experts by subject area, which may lead to future research, teaching or participation in doctoral thesis committees. In the same way, it can be used so that managers and practitioners can detect lines of work related to their needs. This could help to reduce the gap between business and university, promoting mutual collaboration. Finally, if this work is replicated in the coming years, we will have a quick approximation of how the priority interests evolve for a group of national researchers.